A Design Thinking Approach to Teaching Sustainability. (December 2022) - Manna, Valerie; Rombach, Meike; Dean, David; Rennie, Hamish G.
Understanding sustainability requires a system-wide perspective to guide the interpretation of problems and conceptualization of solutions. A lake sustainability Trust provided an opportunity for students to gain this perspective by examining societal, commercial, and environmental policy perspectives associated with a local endangered lake and surrounding wetlands. This was an ideal project to bring sustainability issues to life for students but was too complex for a single class to attack. This article describes a multicourse initiative that sought to heighten students' awareness of sustainability issues using a design thinking problem-solving approach. Interviews conducted revealed concerns that educators may have in considering similar projects. The authors respond to these perceived obstacles with recommendations and a discussion of mitigation strategies. In addition to the Trust gaining direction, the design and implementation of this cross-course experiential learning initiative allowed Marketing Research and Product Design students to develop an appreciation for macrolevel sustainability issues, and environmental policy students to appreciate the value of marketing research in the development of land use plans.